Penegakan Hukum Tindak Pidana Terorisme dalam Pembajakan Pesawat Udara - Budi, Komang Erru Setia; Sudarto, Sudarto (Neolectura, 2025)
Terrorism has become a serious international threat, and air transportation, particularly aircraft hijacking, is a crucial medium for criminal acts. This study aims to examine the legal norms regarding the regulation and effectiveness of law enforcement for terrorism crimes in the context of aircraft hijacking in Indonesia. Indonesia has ratified the Tokyo Convention (1963), The Hague Convention (1970), and Montreal Convention (1971), and regulates them in Law No. 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism and Law No. 1 of 2009 concerning Aviation. The results of the study indicate that aircraft hijacking inherently contains elements of violence and threats that are characteristic of terrorism. Although the legal framework is in place, law enforcement faces obstacles, particularly related to regulatory weaknesses and criminal sanctions in the Aviation Law that have not provided a maximum deterrent effect. Therefore, a revision of the law is needed to strengthen legal certainty and justice.